2020
DOI: 10.1534/g3.120.401291
|View full text |Cite
|
Sign up to set email alerts
|

Population Differentiation at the PVT1 Gene Locus: Implications for Prostate Cancer

Abstract: Genetic variation in susceptibility to complex diseases, such as cancer, is well-established. Enrichment of disease associated alleles in specific populations could have implications for disease incidence and prevalence. Prostate cancer (PCa) is a disease with well-established higher incidence, prevalence, and worse outcomes among men of African ancestry in comparison to other populations. PCa is a multi-factorial, complex disease, but the exact mechanisms for its development and progression are unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…The expression levels of all three exons were significantly higher in MDA PCa 2b cells than in RWPE1 cells ( Figure 1 ). This is consistent with our previous observation of overexpression of these non-protein coding RNAs in PCa tissues ( 14 , 16 ). We found the concentration of PVT1 exons 4A and 9 to be positively correlated across both MDA PCa 2b and RWPE1 cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The expression levels of all three exons were significantly higher in MDA PCa 2b cells than in RWPE1 cells ( Figure 1 ). This is consistent with our previous observation of overexpression of these non-protein coding RNAs in PCa tissues ( 14 , 16 ). We found the concentration of PVT1 exons 4A and 9 to be positively correlated across both MDA PCa 2b and RWPE1 cells.…”
Section: Discussionsupporting
confidence: 93%
“…It would have made sense to remove it from our 3-marker composite score since the 2-marker score with just PVT1 exon 9 and PVT1 exon 4A had an error rate similar to the 3-marker score. However, we recently reported that PVT1 exon 4B is significantly over expressed in prostate tumors with Gleason score ≥8 as compared to those with Gleason score ≤7 ( 16 ), suggesting that PVT1 exon 4B expression may be well suited for distinguishing between indolent and aggressive PCa. In the absence of data to fully test our assertion, we have chosen to leave PVT1 exon 4B in our composite score in anticipation of improving our ability to distinguish between indolent and aggressive PCa.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our group previously reported that PVT1 exon 9 was differentially expressed in prostate cancer. More specifically, PVT1 exon 9 was overexpressed in prostate cancer tissue [ 18 ]. Furthermore, PVT1 exon 9 expression was reported to be significantly higher in prostate cancer cell lines with an aggressive phenotype [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant alternative splicing of pre-mRNAs is one of the characteristics of cancer [ 16 ]. Previously, we have reported that PVT1 exon 9 is overexpressed in prostate cancer cell lines, especially in aggressively tumorigenic prostate cancer cell lines derived from men of African Ancestry [ 17 ] Furthermore, we have observed that PVT1 exon 9 is significantly overexpressed in prostate cancer tissue relative to both normal prostate tissue and benign prostatic hyperplasia [ 18 ]. Also, we have demonstrated that PVT1 exon 9 induces malignant transformation and resistance to androgen deprivation therapy in prostate epithelial cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%